2018
DOI: 10.1515/zkri-2018-2086
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study on the interaction of small molecules with alkali metal ion-exchanged ETS-10

Abstract: In this paper, we present a systematic quantum-mechanical density functional theory (DFT) study of adsorption of small gas molecules in cation-exchanged Engelhard titanosilicate ETS-10 crystalline materials. Adsorbates with a range of polarities were considered, ranging from polar (H2O), quadrupolar (CO2 and N2), to apolar (CH4) atmospheric gases. Starting from the base-case of Na-ETS-10, other extra framework cations such as Li + , K + , Rb + and Cs + were considered. The DFT calculations were performed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…44 The distances between O-Li, O-Na and O-K are 2.167, 2.515 and 2.888Å, respectively; thus, the distance between the O atom and metal cation is getting farther and farther. This is in line with the DFT study by Pillai et al that showed the adsorbate-cation distance increasing in the order of Li, Na and K. 45 Furthermore, the angle of the cation and CO 2 (M/O]C]O) is nonlinear as shown in Fig. 2, which is in good agreement with the GCMC simulations performed on the NaY system.…”
Section: Resultssupporting
confidence: 90%
“…44 The distances between O-Li, O-Na and O-K are 2.167, 2.515 and 2.888Å, respectively; thus, the distance between the O atom and metal cation is getting farther and farther. This is in line with the DFT study by Pillai et al that showed the adsorbate-cation distance increasing in the order of Li, Na and K. 45 Furthermore, the angle of the cation and CO 2 (M/O]C]O) is nonlinear as shown in Fig. 2, which is in good agreement with the GCMC simulations performed on the NaY system.…”
Section: Resultssupporting
confidence: 90%